2017
DOI: 10.1111/imj.13526
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing in the oldest old inpatients: a retrospective analysis of patients referred for specialist geriatric consultation

Abstract: Polypharmacy is prevalent in oldest old inpatients and prescribing patterns according to prevention versus symptom control appear unaffected by age and frailty status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
3
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
2
3
1
2
Order By: Relevance
“…This study has identified high levels of polypharmacy among the very elderly hospitalised population. The degree of polypharmacy is comparable to that reported in previous Australian studies of patients aged over 70 and 85 years, with levels of polypharmacy in these studies at 52.2% for those aged over 70, and at 51.9% for those aged over 85 versus 50.6% in this study population [1,11]. The level of hyper-polypharmacy in this study and the recent study of those aged 85 and older was significantly greater compared to the results among those aged over 70 years, 31.2%, 34.2% versus 23.8% respectively [1,11].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This study has identified high levels of polypharmacy among the very elderly hospitalised population. The degree of polypharmacy is comparable to that reported in previous Australian studies of patients aged over 70 and 85 years, with levels of polypharmacy in these studies at 52.2% for those aged over 70, and at 51.9% for those aged over 85 versus 50.6% in this study population [1,11]. The level of hyper-polypharmacy in this study and the recent study of those aged 85 and older was significantly greater compared to the results among those aged over 70 years, 31.2%, 34.2% versus 23.8% respectively [1,11].…”
Section: Discussionsupporting
confidence: 87%
“…The degree of polypharmacy is comparable to that reported in previous Australian studies of patients aged over 70 and 85 years, with levels of polypharmacy in these studies at 52.2% for those aged over 70, and at 51.9% for those aged over 85 versus 50.6% in this study population [1,11]. The level of hyper-polypharmacy in this study and the recent study of those aged 85 and older was significantly greater compared to the results among those aged over 70 years, 31.2%, 34.2% versus 23.8% respectively [1,11]. The medication burden in this population (7.7 medications per day) was similar to those aged over 85 years (8.3 medications per day) and higher than for those aged over 70 years (7.1 medications per day) [1,11].…”
Section: Discussionsupporting
confidence: 87%
“…It is important to determine whether reduced antibiotic dosages in those with identified risk factors for complications, such as EGFR ≤ 90 mL/min and female gender, could reduce the toxicity but maintain the effectiveness of antibiotic regimens in Australian patients. Furthermore, the safety and effectiveness of alternative agents with demonstrated effectiveness against M. ulcerans, such as bedaqueline, 37 clofazamine 38 and avermectins, 39 could be explored to determine if their use may reduce treatment toxicity without compromising effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Но, как любые препараты, новые ЛС могут стать причиной возникновения нежелательных реакций (НР). Следует учесть, что у пациентов старшей возрастной группы цель фармакотерапии смещается в сторону контроля симптомов заболеваний, улучшения качества жизни и минимизации использования ЛС [1]. Это особенно важно в аспекте полипрагмазии -одновременного назначения пациенту нескольких наименований ЛС 1 , последствиями которой являются повышение риска развития НР, увеличение заболеваемости и смертности, а также риска госпитализации или ее продления [1,2].…”
unclassified
“…Так, по мнению Walckiers D. [3], при назначении 5 и менее ЛС риск развития НР не превышает 5 %, а при применении 6 и более ЛСувеличивается до 25 %. Другими авторами 1 Приказ Минздрава России от 2 ноября 2012 г. № 575н «Об утверждении Порядка оказания медицинской помощи по профилю «клиническая фармакология».…”
unclassified